CONVERT BRAILLE TEXT FROM ARABIC APPLICATION - Noor Ali Alhelaly (European Journal of Interdisciplinary Research and Development, 2022)
A language is means one or the most important ways of communication used by humans, and because blind people need to communicate with others or interact with their environment, Braille provides a lot of properties that help them read texts written in braille, whether books or paper texts. because in the era of technological and cognitive development and making the most of braille text in dealing with the blind, we will provide a set of algorithms that have been formulated in this research paper to be inserted into the computer in a digital scanner or digital imaging method , then applying algorithms to convert image to binary by using mane equation and set step of morphology from text segmentation and characters then excellence , discovering braille text and translating it into the corresponding Arabic text available for use in any application sent to someone else or speaking . we use the result of truth our algorithm exceeded 97%. we hope it will be applied in real life to help people with special needs.